قرآن کی فنّی و تصویری اعجازیت: ڈاکٹر نورالدین عترؒ کی کتاب علوم القرآن الکریم کے تناظر میں تحقیقی مطالعہ: The Artistic and Imagery Miraculousness of the Qur’an: An Analytical Study in the Light of Dr. Nūr al-Dīn Iṭr’s Ulūm al-Qur’ān al-Karīm (Al-Aasar, 2025)
This research explores the artistic and imagery miraculousness (al-iʿjāz al-fannī wa al-taṣwīrī) of the Qur’an as explained by Dr. Nūr al-Dīn Iṭr in his renowned work Ulūm al-Qur’ān al-Karīm. Dr. Iṭr emphasizes that Qur’anic imagery is not a product of external rhetoric or stylistic ornamentation but an inherent manifestation of divine revelation. Through his analysis, he demonstrates how the Qur’an transforms abstract meanings into vivid, living images that engage both intellect and emotion. Words, sounds, and structures in the Qur’an are imbued with a dynamic harmony that evokes sensory and emotional responses, allowing readers to visualize events as if they are witnessing them directly. This study examines Dr. Iṭr’s interpretation of Qur’anic imagery at linguistic, structural, and phonetic levels, highlighting examples that reveal the Qur’an’s inimitable eloquence. It also bridges traditional exegesis with modern literary criticism, emphasizing the artistic coherence of divine speech. The findings indicate that Qur’anic imagery operates as a living art form that reflects both the universality and timelessness of revelation. Ultimately, Dr. Iṭr’s perspective reinforces that the Qur’an is not only a text to be read or understood but also a divine experience to be felt, seen, and lived — a miracle of expression that continues to inspire hearts and intellects across all ages.